IN THIS ISSUE (The Strategic Review for Southern Africa, 2020)
South African Finance Ministers (notably in the plural, given the events since December 2015) face multiple challenges. They deal not only with an economy in stagnation through an austerity policy as recently presented by Pravin Gordhan in his Medium Term Budget in late October, but also with the sobering results of the limited socio-economic transformation since the end of apartheid. The contradictions prevailing since then are reflected not least in the devastating crisis sweeping across South Africa universities. As if that is not enough, a Finance Minister concerned about good governance is also waging an uphill battle to reduce damage by trying to protect the state and its assets from further capture by predatory elites. Considering all of this, it is not surprising that a critical analysis of what is termed economic freedom, an interpretation of the meaning and its consequences, is a fitting contribution to the Strategic Review. Joleen Steyn Kotze presents such an examination in the first article of this issue. Her reflections compare and juxtapose the different notions and ideologies of economic freedom and the effects these may have if turned into policy. This invites further debate regarding the transformation of South African society, which inherited one of the most grossly unequal societies in our world, a condition yet to be markedly reduced.Debates are also required about other aspects that are relevant for a journal focused on regional strategic issues. These include not least the notion of human security and the role of the military. Thuso Benton Mongwaketse relates directly with his contribution, to a subject raised in recent issues.1) By concluding that "security and human security in particular, is fundamentally about responsiveness, accountability, and transparency in governance", he more than indirectly links the discourse on the role of a national defence force to the socio-economic dimensions dealt with in the first article.